Career development as a partner in nation building Australia : origins, history, and foundations for the future - Patton, Wendy, 1957- (Career development series (Rotterdam, Netherlands) ;, 2019)
"Despite examples of vocational guidance practice being evident in Australia since the mid-1800s, there remains a spasmodic and patchwork approach to practice across the country. For decades it is a field which has been paradoxically boosted and challenged by changing economic and political agendas. Repeated international, national and State reviews emphasise the vital nature of a systemic national approach to career development, however authors repeatedly lament the lack of a sustained focus on career activity as a major national priority. There is no broad comprehensive historical reckoning of the history of career development theory and practice in Australia since this early period. Career development theory and practice in Australia has been forged in partnership with developments in an international context. In documenting the shared history with other countries, the author significantly adds to the body of knowledge on career development as a field in Australia and internationally. The book provides new understandings about the historical development of this field of knowledge, and in particular the challenging and cyclical nature of its policy history"--